A 73% Peak PDP Single-Photon Avalanche Diode Implemented in 110 nm CIS Technology With Doping Compensation - Lee, Myung-Jae; Karaca, Utku; Kizilkan, Ekin; Bruschini, Claudio; Charbon, Edoardo (IEEE journal of selected topics in quantum electronics, 2024)
In this article, we present 10 μ m diameter SPADs fabricated in 110 nm CIS technology based on an N + /HVPW junction, with enhanced sensitivity at short wavelengths. To reduce tunneling noise due to the highly-doped layers in the process, a doping compensation technique is used, which allows to adjust the doping profile of the HVPW. Thanks to this technique, DCR is reduced by a factor of 24 at 2 V excess bias voltage when compared to non-compensated devices. Furthermore, the maximum achievable PDP is enhanced by 49% thanks to the much lower DCR leading to a PDP of 73%, the highest ever reported at 440 nm, while the DCR is 12.5 cps/ μ m 2 , all at the 5 V excess bias. Since the junction is formed very close to the surface, the SPAD has excellent sensitivity in the UV spectrum, with a PDP of 43% at a wavelength of 350 nm. The proposed SPAD also achieves a PDP of 7% with a timing jitter of 68 ps at 850 nm at 5 V excess bias, which makes the device very useful for RGB-Z (RGB-D) sensors.